The Glacial Fjord of Ilulissat: The Touristic Development of a Natural Heritage Site - Poiret, Andréa (Études caribéennes, 2024)
Tourism started slowly in Ilulissat (Greenland) in the 1980s‑1990s, before expanding further in the 21st century since the UNESCO classification of the Sermeq Kujalleq Glacier Fjord and the fact that the Arctic has become a symbol of climate change. These journeys are both imaginary, described as “cryotropism”, “borealism” or “nordicity”, and very real: the impact of tourism is visible in the environment. A new international airport is planned for 2023. What type of tourist and therefore travel will this attract? We asked ourselves to what extent the Ilulissat natural site could be managed in a sustainable way. In order to answer this question, we adopted the participant observation from an immersion in the Ilulissat Fjord Office and conducted about twenty semi structured interviews. Le tourisme a commencé lentement à Ilulissat (Groenland) dans les années 1980-1990, avant de s'étendre davantage au XXIème siècle depuis la classification par l'UNESCO du fjord du glacier Sermeq Kujalleq et le fait que l'Arctique soit devenu un symbole du changement climatique. Ces voyages sont à la fois imaginaires, décrits comme du « cryotropisme », du « boréalisme » ou de la « nordicité », et très réels : l'impact du tourisme est visible dans l'environnement. Un nouvel aéroport international est prévu pour 2023. Quel type de touriste et donc de voyage cela attirera-t-il ? Nous nous sommes demandés dans quelle mesure le site naturel d'Ilulissat pourrait être géré de manière durable. Pour répondre à cette question, nous avons adopté l'observation participante lors d'une immersion dans le Bureau du Fjord d'Ilulissat et avons réalisé une vingtaine d'entretiens semi-structurés.